SISTEM PENJADWALAN MATA PELAJARAN MENGGUNAKAN ALGORITMA GENETIKA SMK PGRI RAWALUMBU - Aida Fitriyani; Hendarman Lubis; Andy Achmad Hendharsetiawan; Johanes Andi Lawrence Hutahaean (Jurnal Manajamen Informatika Jayakarta, 2025)
Subject Scheduling System Using the Genetic Algorithm at SMK PGRI Rawalumbu. Bekasi. Faculty of Computer Science. Bhayangkara University, Jakarta Raya. 2024. The aim of this research is to reduce the time required to develop and test schedules. Ensure there are no clashes in the teaching schedule. Utilizing web -based technology for easy and flexible data access. Helps schools compile subject schedules that suit their needs, reduce clashes, and increase the efficiency of automatic schedule creation Research Framework Method or strategy for planning and implementing research that focuses on collecting and analyzing quantitative data. This framework is intended to regulate the procedures required in research and provide an overview of the detailed steps that will be part of the research. A genetic algorithm is an algorithm that uses an understanding of natural evolution to solve problems. By using natural selection theory, genetic algorithms can optimize scheduling system uses a genetic algorithm cycle flow diagram, which includes initial population generation, fitness, level assessment, selected individuals, cross-over, mutation, and regeneration.